Pengaruh Suhu Terhadap Sifat Listrik Polimer Konduktif Polianilin TiO2 Berpenguat Nano Serat Pinang - Afri, Hafiza Rahmi Zul; Mahyudin, Alimin (Universitas Andalas, 2024)
This research serves to see the effect of temperature on conductive polymers, and the temperature variations used are 27 ℃, 37 ℃, 47 ℃, 55 ℃, 67 ℃, and 77 ℃. The polyaniline used is pure polyaniline and a mixture of polyaniline, TiO2, and nano areca fiber with a mixture percentage of 70%: 27%: 3%. Polyaniline is produced from polymerization of aniline monomer and ammonium peroxydisulfate and nano arecafibers are used from nano arecafibers that have been produced in previous research. Electrical properties testing consisted of electrical conductivity and capacitance tests using an LCR meter. The results showed the lowest conductivity value at 27 ℃ was 0.18 × 10-2 S /cm, and the highest conductivity value at 77 ℃ was 1.22 × 10-2 S/cm for pure polyaniline, while the mixed polyaniline obtained the lowest conductivity value at 27 ℃ was 0,85 × 10-2 S/cm, and the highest value at 77 ℃ was 3.61 × 10-2 S/cm. For the capacitance test, the highest value was obtained at 6.8 μF and 18.9 μF. From the results obtained, the higher the temperature, the higher the conductivity value produced, while the capacitance results show that the higher the temperature used, the lower the capacitance value.